Effect of Different Hydrothermal Temperatures on the Properties on Nano-Silica (SiO2) of Rice Husk - Irzaman Irzaman; Irmansyah Irmansyah; Siti Aisyah; Nazopatul Patonah Har; Aminullah Aminullah (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
Rice husk has high silica (SiO2) content and can be used as the primary material for making nano-silica. One of the methods for synthesizing nano-silica was the hydrothermal method. The objective of this study was to synthesize nano-silica from rice husks by observing the effect of temperature in the hydrothermal process on the structure, electrical and particle properties of nano-silica. The hydrothermal process temperature was 150, 200, and 250 °C for 4 hours. The results showed that all nano-silicas were in the amorphous phase. The particle size was in the range of 0.16-13.49 nm with more uniform size distribution on nano-silicas of 200 °C and 250 °C than nano-silica at 150 °C. These three nano-silicas were included in the semiconductor category by increasing temperature and frequency. In addition, these treatment variations resulted 200 °C for 4 hours and pressure of 2 atm as the optimum treatment for manufacturing nano-silica of rice husk ash. This nano-silica could be used as semiconductor material for electronic industry.